Invasive Versus Medical Management in Patients With Prior Coronary Artery Bypass Surgery With a Non-ST Segment Elevation Acute Coronary Syndrome: A Pilot Randomized Controlled Trial. (August 2019) - Lee, Matthew M.Y.; Petrie, Mark C.; Rocchiccioli, Paul; Simpson, Joanne; Jackson, Colette E.; Corcoran, David S.; Mangion, Kenneth; Brown, Ammani; Cialdella, Pio; Sidik, Novalia P.; McEntegart, Margaret B.; Shaukat, Aadil; et al.
Abstract : Background: The benefits of routine invasive management in patients with prior coronary artery bypass grafts presenting with non-ST elevation acute coronary syndromes are uncertain because these patients were excluded from pivotal trials. Methods: In a multicenter trial, non-ST elevation acute coronary syndromes patients with prior coronary artery bypass graft were prospectively screened in 4 acute hospitals. Medically stabilized patients were randomized to invasive management (invasive group) or noninvasive management (medical group). The primary outcome was adherence with the randomized strategy by 30 days. A blinded, independent Clinical Event Committee adjudicated predefined composite outcomes for efficacy (all-cause mortality, rehospitalization for refractory ischemia/angina, myocardial infarction, hospitalization because of heart failure) and safety (major bleeding, stroke, procedure-related myocardial infarction, and worsening renal function). Results: Two hundred seventeen patients were screened and 60 (mean±SD age, 71±9 years, 72% male) were randomized (invasive group, n=31; medical group, n=29). One-third (n=10) of the participants in the invasive group initially received percutaneous coronary intervention. In the medical group, 1 participant crossed over to invasive management on day 30 but percutaneous coronary intervention was not performed. During 2-years' follow-up (median [interquartile range], 744 [570–853] days), the composite outcome for efficacy occurred in 13 (42%) subjects in the invasive group and 13 (45%) subjects in the medical group. The composite safety outcome occurred in 8 (26%) subjects in the invasive group and 9 (31%) subjects in the medical group. An efficacy or safety outcome occurred in 17 (55%) subjects in the invasive group and 16 (55%) subjects in the medical group. Health status (EuroQol 5 Dimensions) and angina class in each group were similar at 12 months. Conclusions: More than half of the population experienced a serious adverse event. An initial noninvasive management strategy is feasible. A substantive health outcomes trial of invasive versus noninvasive management in non-ST elevation acute coronary syndromes patients with prior coronary artery bypass grafts appears warranted. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01895751. Abstract : Supplemental Digital Content is available in the text.